Central Nervous System HIV Infection in “Less-Drug Regimen” Antiretroviral Therapy Simplification Strategies - Ferretti, Francesca; Gianotti, Nicola; Lazzarin, Adriano; Cinque, Paola (Seminars in Neurology, 2014)
Less-drug regimens (LDR) refer to combinations of either two antiretroviral drugs or ritonavir-boosted protease inhibitor (PI) monotherapy. They may represent a simplification strategy in patients with persistently suppressed human immunodeficiency virus (HIV) viremia, with the main benefits of reducing drug-related toxicities and costs. Systemic virological efficacy of LDR is slightly lower as compared with combined antiretroviral therapy (cART), but patients with failure do not usually develop drug resistance and resuppress HIV replication after reintensification. A major concern of LDR is the lower efficacy in the virus reservoirs, especially in the central nervous system (CNS), where viral compartmentalization and independent evolution of infection may lead to CNS viral escape, often associated with neurologic symptoms. The authors reviewed studies of virological and functional CNS efficacy of LDR, particularly of boosted PI monotherapy regimens, for which more information is available. Symptomatic viral CSF escape was observed mainly in PI/r monotherapy patients with plasma failure and low nadir CD4+ cell counts, and resolved upon reintroduction of triple drug cART, whereas asymptomatic viral failure in CSF was not significantly more frequent in patients on PI/r monotherapy compared with patients on standard cART. In addition, there was no difference in functional outcomes between PI monotherapy and cART patients, irrespective of CSF viral escape. More data are needed on the CNS effect of dual ART regimens and, in general, on long-term efficacy of LDR. Simplification with LDR may be an attractive option in patients with suppressed viral load, if they are well selected and monitored for potential CNS complications.
Keywords: cerebrospinal fluid; cerebrospinal fluid viral escape; central nervous system; monotherapy; dual therapy